General Monitoring of Observational Units in the Arctic Tundra - Karlstrøm, Erlend Melum (UiT Norges arktiske universitet, 2021)
Climate change is going to change what we know about the arctic tundra. Patterns in the behavior of the wildlife that lives there are predicted to undergo a shift, and it will therefore be important to have reliable sources of empirical data, so that we can understand how these developments are playing out. The arctic tundra is remote and difficult to deploy sensing instruments on, and signal coverage is unreliable. Finding a way to monitor them reliably from a distance is needed. This thesis describes how a prototype for a Wireless Sensor Network was designed, implemented, and tested, with the aim of connecting Observational Units together in a local cluster, and cooperate amongst themselves to propagate monitoring data to external servers. The system was designed so that nodes can dynamically discover neighboring nodes within their range, and gossip knowledge about where sinks are in the network. Sinks are nodes which have managed to establish a link with an external server, and the paths to these sinks are spread across the network. Such that if only node in the entire cluster is a sink, then data from every node has a path outside of the cluster. Results from running validation shows that the implemented prototype func- tions as intended, but experiments have revealed apparent weaknesses. The number of paths which are shared in gossiping shows an exponential growth when the number of nodes in a cluster grows linearly. The experiments into bundling and monitoring-data propagation shows that combining data together causes a reduction in these types of transmissions by a factor equal to that of the number of data fragments which are combined, however the Partial Bundle Policy measure to increase throughput for fringe nodes has unexpected consequences. The prototype system works as intended per the design. We have found however that the system is not scalable due to the extent of the accumulated path knowledge. Suggestions for avenues to address this has been outlined in the discussion chapter. There is a need ...